Do Lonely Days Invade the Nights? Potential Social Modulation of Sleep Efficiency - Cacioppo, John T.; Hawkley, Louise C.; Berntson, Gary G.; Ernst, John M.; Gibbs, Amber C.; Stickgold, Robert; Hobson, J. Allan (Psychological Science, 2002)
Loneliness predicts morbidity and mortality from broad-based causes, but the reasons for this effect remain unclear. Few differences in traditional health behaviors (e.g., smoking, exercise, nutrition) have been found to differentiate lonely and nonlonely individuals. We present evidence that a prototypic restorative behavior–sleep–does make such a differentiation, not through differences in time in bed or in sleep duration, but through differences in efficacy: In the study we report here, lonely individuals evinced poorer sleep efficiency and more time awake after sleep onset than nonlonely individuals. These results, which were observed in controlled laboratory conditions and were found to generalize to the home, suggest that lonely individuals may be less resilient than nonlonely individuals in part because they sleep more poorly. These results also raise the possibility that social factors such as loneliness not only may influence the selection of health behaviors but also may modulate the salubrity of restorative behaviors.